Experiments and numerical calculation to determine aerodynamic characteristics of flows around 3D wings - Son, Nguyen Hong; Ngoc, Hoang Thi Bich; Phong, Dinh Van; Hung, Nguyen Manh (Vietnam Journal of Mechanics, 2014)
The report presents method and results of experiments in wind tunnel to determine aerodynamic characteristics of 3D wings by measuring pressure distribution on the wing surfaces. Simultaneously, a numerical method by using sources and doublets distributed on panel elements of wing surface also is carried out to calculate flows around 3D wings. This computational method allows solving inviscid problems for wings with thickness profile. The experimental and numerical results are compared to each other to verify the built program that permits to extend the range of applications with the variation of wing profiles, wing planforms, and incidence angles.